2020
DOI: 10.1111/ajag.12795
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a ‘Safe Recovery’ fall prevention program: Refining intervention theory using realist methods

Abstract: Objectives: This research aimed to explain how the Safe Recovery Programme (SRP) may best work to reduce falls in older adults undergoing rehabilitation in four wards in an older person's health and rehabilitation service. Methods: Qualitative realist methods were used, including surveys completed by patients and staff, and qualitative interviews or focus groups exploring views of patients, ward staff and SRP educators. Results: Emphasising different types of information for patients with different preexisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(45 citation statements)
references
References 26 publications
2
43
0
Order By: Relevance
“…A more commonly measured impact was patient knowledge. Seven studies measured patient understanding of their falls risks and care plan with varied results (23,43,53,54,61,63, 65) e.g., Radecki et al ( 54) conducted a knowledge-in-action survey which showed statistically signi cant improvements between baseline and intervention groups (P = .0007) in patient involvement in care planning. However, there was no signi cant difference in other questions, including whether the prevention plan was always followed.…”
Section: To What Extent Do Patients Participate In Falls Prevention P...mentioning
confidence: 99%
See 4 more Smart Citations
“…A more commonly measured impact was patient knowledge. Seven studies measured patient understanding of their falls risks and care plan with varied results (23,43,53,54,61,63, 65) e.g., Radecki et al ( 54) conducted a knowledge-in-action survey which showed statistically signi cant improvements between baseline and intervention groups (P = .0007) in patient involvement in care planning. However, there was no signi cant difference in other questions, including whether the prevention plan was always followed.…”
Section: To What Extent Do Patients Participate In Falls Prevention P...mentioning
confidence: 99%
“…The quality of interaction between patients and professionals appeared to underpin successful messaging (53,54), enabling patients to express the circumstances that constrained their participation. However, creating this interactional space appeared to rely on staff experience, skills, and timeresources that may be limited outside a study context (53,54). Furthermore, some patients are not able to remember or understand messaging due to cognitive impairment, with one study indicating potential harm to these patients (49).…”
Section: Programme Theory Re Nementmentioning
confidence: 99%
See 3 more Smart Citations